258 Design and validation of a recurrence risk predicting score in early stage cervical cancer after radical hysterectomy. (4th December 2020) - Manzour, Nabil; Chacon, Enrique; Martín-Calvo, Nerea; Mínguez, José Ángel; Castellano, Teresa; Vazquez, Daniel; Salas, Diego; Gonzalez-Martin, Antonio; Alcazar, Juan Luis; Chiva, Luis M
Abstract : Introduction/Background: After the LACC trial, the scientific evidence has focused on confirming and finding the cause of why the open route presents better results than minimally invasive surgery (MIS). Even though the independent factors involved in relapse has not been studied. Methodology: Primary objective: to know the independent clinical, surgical and anatomopathological factors involved in the relapse of patients with stage IB1 cervical cancer who underwent radical hysterectomy (2013–2014). Secondary objective: To create a risk predictive index (RPI) that allows us to better select and stratify patients with a higher probability of relapse. Methods: Starting from 1272 patients from the European database belonging to the SUCCOR study and after applying the different inclusion and exclusion criteria we obtained 1156 patients. We randomly divided our sample into a test group and a validation group in a proportion of 60% to 40%. The test group was used to identify the variables independently associated with relapse and to define the relapse RPI. The RPI was applied to calculate a relapse risk score for each participant in the validation group. According to their risk of relapse, participants were classified into 3 risk groups. Results: Women who relapse are more likely to have tumours larger than 2 cm on imaging assessment (OR 2.15, 95% CI 1.33- 3.5) and to undergo MIS (OR 1.61, 95% CI 1.00- 2.57). On the other hand, conisation is inversely associated with the risk of relapse (OR 0.31, 95% CI 0.17- 0.60). The AUC in the validation group for RPI is (0.72; 95% CI 0.65- 0.79). Depending on their score, patients were classified at low, medium or high risk of relapse. The relapse rate observed in each group was 3.4%, 9.8% and 21.3% respectively. With a median follow-up of 58 months, the mean DFS in the validation group for low, medium and high risk categories were 75.4 (95% CI 73.8- 76.9), 75.5 (95% CI 72.4- 78.5) and 64.1 (95% CI 59.4- 68.9) months respectively (P < 0.001). Conclusion: Our risk predictor index proved to be valid and therefore may help to identify those patients who would benefit from adjuvant therapy and close follow-up after radical hysterectomy.